2010
DOI: 10.1586/ern.10.115
|View full text |Cite
|
Sign up to set email alerts
|

Fear reduction in patients with chronic pain: a learning theory perspective

Abstract: Acute pain informs the individual that there is an imminent threat of body damage, and is associated with the urge to escape and avoid. Fear learning takes place when neutral stimuli receive the propensity to predict the occurrence of pain, and when defensive responses are initiated in anticipation of potential threats to the integrity of the body. Fear-avoidance models have been put forward featuring the role of individual differences in catastrophic interpretations of pain in the modulation of learning and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 111 publications
1
48
0
8
Order By: Relevance
“…Both pain catastrophizing and FABs are key components of the Fear-Avoidance Model,54 which has been used extensively to explain the development of pain and disability in patients with MSK pain. However, although strong evidence exists for the predictive value of each of these model components,55,56 studies investigating the causal nature of these relationships have suggested that the model does not work in the hypothesized order 57,58. This model was not tested in full as part of the present study, but the results add to the evidence base for FABs being potential mediators of treatment outcome, even though the exact pathways through which this factor contributes has not been fully clarified as yet.…”
Section: Discussionmentioning
confidence: 99%
“…Both pain catastrophizing and FABs are key components of the Fear-Avoidance Model,54 which has been used extensively to explain the development of pain and disability in patients with MSK pain. However, although strong evidence exists for the predictive value of each of these model components,55,56 studies investigating the causal nature of these relationships have suggested that the model does not work in the hypothesized order 57,58. This model was not tested in full as part of the present study, but the results add to the evidence base for FABs being potential mediators of treatment outcome, even though the exact pathways through which this factor contributes has not been fully clarified as yet.…”
Section: Discussionmentioning
confidence: 99%
“…Learning theory posits that the aversive signal of pain may be passed to neutral stimuli (like physical movement behaviors), which contributes to avoidant behavior. In vivo exposure therapy extinguishes threat, fear, and behavioral avoidance through progressively increasing engagement in painful behaviors in the absence of catastrophic outcomes; when these behaviors are performed without serious negative consequences, patients may realize that their expectations about the consequences of physical movement and pain are unrealistic 24,42. Consistent with exposure treatments for phobias and other anxiety disorders, in vivo exposure treatment for fear of pain involves development of a personalized, graded hierarchy of activities that elicit a fearful response, psychoeducation related to pain, fear, and behavior, and ultimately slow and systematic exposure to activities related to the individual’s fear hierarchy 41.…”
Section: Psychological Intervention As An Approach To Pain Managementmentioning
confidence: 99%
“…Fear and anxiety also have a significant role in both acute and chronic pain (Ploghaus et al, 1999; den Hollander et al, 2010). The expectation of the pain modulates (usually increases) the pain sensation as well as playing a role in anxiety and phobia (Ploghaus et al, 2003).…”
Section: Habenula and Behaviors Associated With Chronic Painmentioning
confidence: 99%